Platelet Hypersensitivity in Acute Malaria (Plasmodium falciparum) Infection in Man - Essien, E M; Ebhota, M I (Thrombosis and Haemostasis, 1981)
During acute malaria infection, platelets in human platelet-rich plasma are hypersensitive to the addition of ADP between 1.0 uM and 5.0 uM, or adrenaline 0.11 uM as aggregating agents. The mean maximum aggregation amplitude (as % of light transmission) obtained from 8 subjects in response to added ADP (1.0 uM), 39.8 ± 27 (1SD), was significantly greater than the value in 6 controls (5.2±6.7 (1SD); t = 3, 51 P <0.005). A similar pattern of response was obtained with higher ADP concentrations (2.4,4.5 or 5.0 uM) in 22 patients and 20 control subjects (89.9±14.9% vs 77.8±16.5% (1SD) t = 2.45, P <0.02). Addition of 4.5 uM ADP to patient PRP usually evoked only a single aggregation wave (fused primary and secondary waves) while the typical primary and secondary wave pattern was usually obtained from controls.Mean plasma B-thromboglobulin (BTG) concentration in 7 patients (208.3 ± 15.6 ng/ml) was significantly higher than the value in 6 control subjects (59.2±15.7 ng/ml; t = 13.44, P <0.002).
Keywords: Platelet hypersensitivity; Acute malaria infection